A single-source shortest path algorithm for dynamic graphs. Issue 3 (1st September 2020) - Alshammari, Muteb; Rezgui, Abdelmounaam
Abstract: Graphs are mathematical structures used in many applications. In recent years, many applications emerged that require the processing of large dynamic graphs where the graph's structure and properties change constantly over time. Examples include social networks, communication networks, transportation networks, etc. One of the most challenging problems in large scale dynamic graphs is the single-source shortest path (SSSP) problem. Traditional solutions (based on Dijkstra's algorithms) to the SSSP problem do not scale to large dynamic graphs with a high change frequency. In this paper, we propose an efficient SSSP algorithm for large dynamic graphs. We first present our algorithm and give a formal proof of its correctness. Then, we give an analytical evaluation of the proposed solution.